Prematurity, asphyxia and congenital malformations underrepresented among neonates in a tertiary pediatric hospital in Vietnam - Kruse Alexandra Y; Ho Binh TT; Phuong Cam N; Stensballe Lone G; Greisen Gorm; Pedersen Freddy K (BMC, 2012)
Abstract Background Estimated 17,000 neonates (≤ 28 days of age) die in Vietnam annually, corresponding to more than half of the child mortality burden. However, current knowledge about these neonates is limited. Prematurity, asphyxia and congenital malformations are major causes of death in neonates worldwide. To improve survival and long term development, these vulnerable neonates need access to the specialized neonatal care existing, although limited, in lower middle-income countries like Vietnam. The aim of this study was to describe these conditions in a specialized Vietnamese hospital, compared to a Danish hospital. Methods We performed a comparative observational study of all neonates admitted to a tertiary pediatric hospital in South Vietnam in 2009-2010. The data were prospectively extracted from the central hospital registry and included basic patient characteristics and diagnoses (International Classification of Diseases, 10th revision). Prematurity, asphyxia and designated congenital malformations (oesophageal atresia, gastroschisis, omphalocoele, diaphragmatic hernia and heart disease) were investigated. In a subgroup, the prematurity diagnosis was validated using a questionnaire. The hospitalization ratio of each diagnosis was compared to those obtained from a Danish tertiary hospital. The Danish data were retrieved from the neonatal department database for a ten-year period. Results The study included 5763 neonates (missing<1%). The catchment population was 726,578 live births. The diagnosis was prematurity in 7%, asphyxia in 2% and one of the designated congenital malformations in 6%. The diagnosis of prematurity was correctly assigned to 85% of the neonates, who were very premature or had very low birth weight according to the questionnaire, completed by 2196 neonates. Compared to the Danish Hospital, the hospitalization ratios of neonates diagnosed with prematurity (p<0.01), asphyxia (p<0.01) and designated congenital malformations (p<0.01- 0.04) were significantly lower. Conclusion Our findings suggest the investigated diagnoses were underrepresented in the Vietnamese study hospital. In contrast, relatively mild diagnoses were frequent. These results indicate the use of specialized care may not be optimal. Pre-hospital selection mechanisms were not investigated and additional studies are needed to optimise utilisation of specialized care and improve neonatal survival.